Effect of Heritability, Genetic Advance and Correlation on Yield Contributing Traits in Upland Cotton - Muhammad Bhutta; Muhammad Kamran Qureshi; Muhammad Ishaq; Ali Hassan; Sana Munir; Ahmad Shahzad; Muhammad Anjam (Journal of Agricultural Sciences)
This research was planned to study the heritability (broad sense), correlation, genetic advance and behavior of different characters in segregating population of upland cotton. The material consists of segregating population of fourteen crosses along with their seven parents. Parental varieties and segregating population show significant difference for all traits under the study. Plant height, ginning out turn (GOT), bolls per plant and yield per plant showed heritability ranging from 78.9 to 27.3. Significant genotypic correlation of yield with plant height was 0.698, bolls per plant was 0.930, GOT was 0.692, fiber strength was 0.548 and with fiber fineness was 0.435. Phenotypic correlation of yield per plant with plant height was 0.520, boll per plant was 0.894 and GOT was 0.476. It can be suggested that plant height, GOT and bolls per plant are important yield contributing traits as they are positively correlated with seed cotton yield per plant. High value for bolls per plant, GOT and yield per plant was recorded in BH-167 × V4 and CIM-534 × V4, which can be utilized in future breeding program.